Expropriation risk and technology - Opp, Marcus M. (Journal of Financial Economics, 2012)
This paper develops a unified framework to analyze the dynamics of firm investment in countries with poor legal enforcement. The firm's technology edge over the government generates endogenous property rights. Industry variation in the technology gap predicts a sectoral pecking-order of expropriations. Long-run investment distortions may be Pareto superior relative to persistent investment at the static optimum. The dynamics of investment and transfers depend on whether incentives (backloading) or efficiency (frontloading) concerns dominate at the initial division of surplus. An increase in government efficiency may reduce its welfare. The model provides a technology-driven rationale for the widespread use of conglomerate structures in emerging market countries.